NEXUS Arch: A Multicenter Study Evaluating the Initial Experience With a Novel Aortic Arch Stent Graft System. Issue 2 (10th February 2023) - Planer, David; Elbaz-Greener, Gabby; Mangialardi, Nicola; Lindsay, Thomas; D'Onofrio, Augusto; Schelzig, Hubert; Chaykovska, Lyubov; Hill, Andrew; Holden, Andrew; Antonello, Michele; Tan, Kong T.; Orrico, Matteo; et al.
Abstract : Objective: To assess the initial clinical experience with a novel endograft system (NEXUS Aortic Arch Stent Graft System) designed to treat aortic arch pathologies and address the morphology and hemodynamic challenges of the aortic arch. Summary Background Data: The aortic arch remains the most challenging part of the aorta for both open and endovascular repair. Transcatheter aortic arch repair has the potential to significantly reduce surgical risks. Methods: Patients underwent transcatheter aortic arch repair with a single branch, 2 stent graft system, implanted over a through-and-through guidewire from the brachiocephalic trunk, to the descending aorta with an ascending aorta stent graft. The ascending aorta stent graft is deployed into a designated docking sleeve to connect the 2 stent grafts and isolate the aortic arch pathology. Proximal landing zone in all cases was in Zone 0. Anatomical inclusion criteria included adequate landing zone in the ascending aorta, brachiocephalic trunk, and descending thoracic aorta. Preparatory debranching procedure was performed in all patients with carotid–carotid crossover bypass and left carotid to left subclavian bypass, or parallel graft from descending aorta to left subclavian artery. Safety and performance were evaluated through 1 year. Survival analysis used the Kaplan–Meier method. Results: Twenty-eight patients, 79% males, with a mean age of 72.2 ± 6.2 years were treated with 100% procedural success. Isolated aortic arch aneurysm was the principle pathology in 17 (60.7%) of patients, while chronic aortic dissection was the principle pathology in 6 (21.4%) of patients. The remaining 5 (17.8%) had combined or other pathologies. At 1 month, the vascular pathology was excluded in 25 of 26 alive patients (96.1%). The 30 days mortality rate was 7.1%, stroke rate was 3.6% (all nondisabling), and combined mortality/stroke rate was 10.7%. One-year mortality was 10.7%, without device or aneurysm-related death. Two patients (7.1%) reported stroke or transient ischemic attack at 1 year that recovered completely. One year combined mortality/stroke rate was 17.8%. There were 3 patients (10.7%) that had device-related unplanned reinterventions through 1 year. Conclusions: The NEXUS Aortic Arch Stent Graft System, a novel single branch, 2 stent graft system used for endovascular aortic arch repair that requires landing in the ascending aorta, demonstrates a high success rate with excellent 1 year safety and performance.